Divergent synthesis of unsymmetrical Bis-heteroaryl ketones via base-promoted cascade reactions of 1,2-alkynedione-derived N-propargylic β-enaminones - Bag, Debojyoti; Saini, Sheetal; Rathod, Mahesh S.; Sawant, Sanghapal D. (JOURNAL OF ORGANIC CHEMISTRY, 2024)
Keywords: ASYMMETRIC-SYNTHESIS; heterocycles; intramolecular cyclization; pyrroles

Divergent synthesis of 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) using DMSO as a single carbon synthon - Sikdar, Papiya; Das, Sourav; Saini, Sheetal; Sawant, Sanghapal D.; Bagdi, Avik Kumar (Organic & Biomolecular Chemistry, 2025)
A divergent approach has been explored for synthesizing 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) using DMSO as a C1 synthon. A library of 3-formylpyrazolo[1,5-a]pyrimidines and methylene-bridged bis(pyrazolo[1,5-a]pyrimidines) has been synthesized using CuOAc and AcOH, respectively. The reaction progressed through a radical pathway. The usefulness of 3-formylpyrazolo[1,5-a]pyrimidines in synthesizing a zaleplon derivative has been demonstrated.